2020
DOI: 10.1002/tqem.21712
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management in Latin America: Systematic literature review and future directions

Abstract: The implementation and scope of green supply chain management (GSCM) practices vary among organizations. In emerging economies, new production chain models are required, but little is known about GSCM in these countries, especially in Latin America. Thus, this paper aims to highlight the state‐of‐the‐art of GSCM in Latin America, through a systematic review of the literature (using Scopus and Web of Science databases) and suggests a research agenda with nine recommendations. Results show underexplored themes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 93 publications
0
10
1
1
Order By: Relevance
“…During production and purchasing, finite resources can pollute the environment, contaminating the air, water, and land. According to Teixeira et al (2020), GP practices cover any initiatives to mitigate the detrimental consequences of a firm's goods or services on the environment. Such endeavors shall increase sustainable environmental performance by minimizing risky materials, reducing environmental accidents, and enhancing communities' well‐being (Gedam et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…During production and purchasing, finite resources can pollute the environment, contaminating the air, water, and land. According to Teixeira et al (2020), GP practices cover any initiatives to mitigate the detrimental consequences of a firm's goods or services on the environment. Such endeavors shall increase sustainable environmental performance by minimizing risky materials, reducing environmental accidents, and enhancing communities' well‐being (Gedam et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Internal GSCM practices G1. Internal Environmental Management (IEM) [20,22,23,34,35] G2. Green Design (GD) [19,[21][22][23]30,[32][33][34][35] G3.…”
Section: Gscm Practices Academic Sourcesmentioning
confidence: 99%
“…Implementing GSCM practices have been consistently found to directly improve the environmental performance of a firm [18]; as a result, GSCM practices have started gaining popularity within industry [19][20][21]. The adoption of GSCM practices offers a promising approach for organizations to be more environmentally friendly and become more sustainable [22]. Therefore, the focus of this study is to determine the state of play regarding the application of GSCM practices in the O&G industry.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, building on this concept, organizations' have ensured establishing supply chain sustainability on multiple levels for gaining sustainable competitive advantage ( 31 ). Given the illustration, the study showed that the supply chain had highlighted the demand for incorporating the sustainable agenda in the business strategy, thereby exploring the market benefits, performance indicators, and sustainable advantage ( 32 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%